Antioxidant activities and total phenolic content of Malaysian herbs as components of active packaging film in beef patties - Wan Amnin, Wan Yahaya; Noraziah, Abu Yazid; Nurul Aini, Mohd Azman; Almajano, María Pilar (MDPI AG, 2019)
Active packaging containing natural extracts is a promising innovation to prolong the shelf life of perishable food. The objective of this work was to develop a bioactive edible film from semi-refined carrageenan (SRC) and glycerol (G) as plasticizer incorporated with natural extract. Five Malaysian herbs were evaluated to determine their total phenolic content (TPC) and antioxidant activities. The Persicaria minor (PM) extract demonstrated the highest TPC (1.629 mg GAE/L sample) and radical scavenging activity evaluated by the radicals 2,2’-azinobis [3-ethylbenzothiazoline-6-sulfonic acid] (27.166 mg TE/L sample), 2,2-diphenyl-1-picrylhydrazyl (719.89 mg eq. Trolox/L sample) and α,α′-Azodiisobutyramidine dihydrochloride (5.81 mg TE/L sample). Thus, PM extract was selected for active packaging film at concentrations of 0.4, 1.0 and 2.0% and compared with 0.4% Butylatedhydroxianisole in 2% SRC and 0.9% G film formulation. The meat patties were wrapped in the films and stored under refrigeration (4 ± 2 °C) for 14 days. The film with 2% PM exhibited significantly lower lipid deterioration analysed by the thiobarbituric acid reactive substance assay (p < 0.05) and small changes in % metmyoglobin value which indicated the minimum development of brown colour (p < 0.05). Hence, this film can be used as a packaging material to improve meat quality characteristics.